Accumulation and toxicity of biologically produced gold nanoparticles in different types of specialized mammalian cells - Pourali, Parastoo; Svoboda, Milan; Neuhöferová, Eva; Dzmitruk, Volha; Benson, Veronika (Biotechnology and applied biochemistry, 2024)
The biologically produced gold nanoparticles (AuNPs) are novel carriers with promising use in targeted tumor therapy. Still, there are no studies regarding the efficacy of nanoparticle internalization by cancer and noncancer cells. In this study, AuNPs were produced by Fusarium oxysporum and analyzed by spectrophotometry, transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDS), and Zetasizer. Obtained AuNPs were about 15 nm in size with a zeta potential of -35.8 mV. The AuNPs were added to cancer cells (4T1), noncancer cells (NIH/3T3), and macrophages (RAW264.7). The viability decreased in 4T1 (77 ± 3.74%) in contrast to NIH/3T3 and RAW264.7 cells (89 ± 4.9% and 90 ± 3.5%, respectively). The 4T1 cancer cells also showed the highest uptake and accumulation of Au (∼80% of AuNPs was internalized) as determined by graphite furnace atomic absorption spectroscopy. The lowest amount of AuNPs was internalized by the NIH/3T3 cells (∼30%). The NIH/3T3 cells exhibited prominent reorganization of F-actin filaments as examined by confocal microscopy. In RAW264.7, we analyzed the release of proinflammatory cytokines by flow cytometry and we found the AuNP interaction triggered transient secretion of tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ). In summary, we proved the biologically produced AuNPs entered all the tested cell types and triggered cell-specific responses. High AuNP uptake by tumor cells was related to decreased cell viability, while low nanoparticle uptake by fibroblasts triggered F-actin reorganization without remarkable toxicity. Thus, the biologically produced AuNPs hold promising potential as cancer drug carriers and likely require proper surface functionalization to shield phagocytizing cells.
Keywords: buňky NIH 3T3; NIH 3T3 Cells; Fusarium; 4T1 cells; stress response; biologically produced gold nanoparticles; Mice; RAW 264.7 buňky; Macrophages; zvířata; nanoparticle uptake; zlato; viabilita buněk; Cell Survival; myši; makrofágy; RAW 264.7 Cells; actin reorganization; Gold; NIH/3T3 cells; Metal Nanoparticles; kovové nanočástice; RAW264.7 cells; Animals